Experience Knowledge and Skills of Housewives in Providing First Aid for Burns - Patressiya, Lita; Ulum, Miftachul; Rachmawati, Dewi; Winarni, Sri (Health Access Journal, 2025)
Burn injuries are common among housewives, but many lack knowledge of proper first aid, and tend to perform inappropriate self-care. This study aims to identify the incidence history and first aid skills of burns. The research design was descriptive quantitative with 44 samples selected through purposive sampling technique. The research was conducted door to door in RT 002 RW 013, Sananwetan Village, Blitar City in January-February 2024. The instruments used were questionnaires to identify the history of the incident and observation sheets to identify burn first aid skills. The results showed that the most common cause of burns was hot oil (56.8%) during cooking (88.6%), mostly occurred on the hands (86.4%) with an area of 1-3 cm (50%), and had no serious impact (93.2%). The most common type of burn was moderate (56.8%) and the most common action was applying toothpaste (29.5%). The results showed that 40.9% (18 respondents) who had experienced mild burns, 56.8% (25 respondents) moderate burns, and 2.3% (1 respondent) severe burns had very poor first aid skills. It was concluded that the history of burns varied and the first aid skills of respondents were poor, so education is needed to increase awareness and skills in dealing with burns in the household.